Adsorption of Acid Fuchsin and Fast Green on Activated Carbons - Ho, Soon Min (2003)
Activated carbons produced from palm oil shell with H3PO4 activation (AC 34) and physical activation (AC 00) were used to adsorb dye solutions, namely Acid Fuchsin and Fast Green. The precursors were carbonized under an inert nitrogen atmosphere for three hours followed by carbon dioxide gas activation for another hour in an electric furnace at 500˚C. Analysis of the adsorption isotherms of N2 at 77 K shows that the surface area of AC 34 (1017 m2/g) is higher than AC 00 (426 m2/g). The average pore diameter for AC 34 and AC 00 is 25.2 and 15.1 Å, respectively. Characterization of activated carbons were studied by using various analytical techniques such as Fourier Transform Infrared (FTIR), Scanning Electron Microscopy (SEM), determination of ash and moisture content. The contact time, adsorbent dosage, adsorbate concentration, temperature and pH of the adsorbate that affecting the adsorption process were also studied. The result shows that the AC 34 is very effective in adsorbing Acid Fuchsin and Fast Green compared to AC 00. The adsorption process agreed to the Langmuir and Freundlich isotherms with endothermic nature. In addition to , the two samples prepared in this study, another two commercial activated carbons (AC 6070 and AC 3040) were also used for comparison. A favorable adsorption of both dye solutions on AC 6070 compared to the other activated carbons is due to its higher BET surface area and micropore volume. The amount of dye adsorbed on adsorbent is in the order of AC 34>AC 00>AC 6070>AC 3040.